EVALUASI YURIDIS SISTEM PENYELESAIAN SENGKETA PEMILIHAN UMUM DAN IUS CONSTITUENDUM PERADILAN KHUSUS PEMILIHAN UMUM - Ulya, Nurul Ula; Musyarri, Fazal Akmal (Justitia et Pax, 2019)
The General Election Judicial System in Indonesia currently runs partially in Indonesia because the institutional structure that plays a role in handling General Election cases consists of elusive anatomy. Some of these institutions include the Constitutional Court, the Election Supervisory Body, the Administrative Court and the District Court which have different portions of authority and lack synergy in their representation. This can lead to miscoordination and overlapping of authority. Therefore, the formation of a Special Election Judicial body is an alternative solution that can be done to maintain the implementation of a democratic General Election up to the stage of case resolution.